The Difference in Abundance of Echinoideas on Coral Ecosystem and Seagrass Beds in Pancuran Belakang, Karimunjawa, Jepara - Suryanti Suryanti; Ruswahyuni Ruswahyuni (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2014)
Phyllum of echinoderms has a large role on the ecosystems of coral reefs and seagrass beds, especially their various roles in foodweb, which are herbivorous covering, carnivorous, or as detritus eaters. One of the echinoderms which is always found in the coralreefs region and seagrass beds is the echinoidea. Echinoidea mostly inhabits coral reef ecosystem and seagrass beds and found onhard substrates, especially in seagrass beds substrates that consist of mixtures of sand and crushed corals. The purpose of thisresearch was to know the difference in the echinoidea abundances of coral reef ecosystem and seagrass beds in Pancuran Belakang,Karimunjawa, Jepara in the month of May 2014. Research methodology that was used is a method of direct observation that is bymeans of observing the species of echinoidea found in coral reef ecosystems and seagrass beds and water quality conditions assupporting data. The research results showed that the cover of coral reefs and seagrass beds in Pancuran Belakang Karimunjawa inthe category of good which are of 55.29 % on coarl reef and 61.94 % seagrass. The echinoidea that was found in reefs and seagrassbeds is Diadema setosum (123;36 ind (150 m)-2), Diadema antilarum (63;18 ind(150 m)-2), Echinothrix calamaris (34;22 ind (150m)-2), Mespilia globulesa (12;0 ind(150 m)-2), and Echinometra mathaei (14;0 ind(150 m)-2), The independent t test with SPSSsignificant value of 5 % t table = 2.776 > t calculated = -2.319. Therefore, Ho was accepted that there is a significant difference ofthe echinoidea on the coral reefs and seagrass beds.Keywords : Echinoideas; Coral Reef; Seagrass, Pancuran Belakang and Karimunjawa